Wear Test Apparatus for Friction and Wear Evaluation Hip Prostheses - Hua, Zikai; Dou, Pingchuan; Jia, Haili; Tang, Fei; Wang, Xiaojing; Xiong, Xin; Gao, Leiming; Huang, Xiuling; Jin, Zhongmin (Frontiers in Mechanical Engineering, 2019)
Wear is a key factor affecting the survivorship of artificial hip joints. Joint wear testers, as called ‘simulators’ are developed to simulate the motions and force of human joints. By using simulators, in vitro wear tests could be performed for artificial joints. This paper introduces a new hip joint simulator developed for the biotribological investigation of artificial hip joints. Friction force measuring module has been set up and assembled to monitor the friction force during the wear tests. Validation tests have been performed using two kinds wear couples of 28mm CoCrMo femoral heads against conventional and X-linked ultra high molecular weight polyethylene (UHMWPE) acetabular cups. The hip joint simulator is a precise and reliable method both for the wear evaluation and biotribological investigation of hip prostheses.